Enhancing postharvest food safety: the essential role of non-thermal technologies in combating fungal contamination and mycotoxins - Molina-Hernandez, Junior Bernardo; Grande-Tovar, Carlos David; Neri, Lilia; Delgado-Ospina, Johannes; Rinaldi, Massimiliano; Cordero-Bueso, Gustavo Adolfo; Chaves-López, Clemencia (Frontiers in Microbiology, 2025)
During the production and storage of agricultural products, molds frequently occur as contaminants that can produce a wide range of secondary metabolites, the most important of which are mycotoxins. To solve these problems, the industry uses various methods, products and processes. This review examines the latest advances in novel non-thermal technologies for post-harvest inactivation of filamentous fungi and reduction of mycotoxins. These technologies include high pressure processes (HPP), ozone treatment, UV light, blue light, pulsed light, pulsed electric fields (PEF), cold atmospheric plasma (CAP), electron beams, ultrasound (US) and nanoparticles. Using data from previous studies, this review provides an overview of the primary mechanisms of action and recent results obtained using these technologies and emphasizes the limitations and challenges associated with each technology. The innovative non-thermal methods discussed here have been shown to be safe and efficient tools for reducing food mold contamination and infection. However, the effectiveness of these technologies is highly dependent on the fungal species and the structural characteristics of the mycotoxins. New findings related to the inactivation of fungi and mycotoxins underline that for a successful application it is essential to carefully determine and optimize certain key parameters in order to achieve satisfactory results. Finally, this review highlights and discusses future directions for non-thermal technologies. It emphasizes that they meet consumer demand for clean and safe food without compromising nutritional and sensory qualities.